ЗНИЖЕННЯ ВИТРАТ НА ПОКРИТТЯ НЕБАЛАНСІВ УЧАСНИКІВ БАЛАНСУЮЧОЇ ГРУПИ ВИРОБНИКІВ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ З ВІДНОВЛЮВАНИХ ДЖЕРЕЛ - Блінов, І.В.; Мірошник, В.О.; Лоскутов, С. C. (Інститут електродинаміки НАН України, Київ, 2023)
The analysis of the peculiarities of the work of the balancing group of electricity producers from renewable energy sources in terms of the distribution of the cost of imbalances. Prerequisites for the introduction of a mechanism to support producers in the form of Feed-in-premium are considered. The advantages and disadvantages of independent participation of the producer in the wholesale electricity market are analyzed. The calculations show that when leaving the balancing group of SE "Guaranteed Buyer" it is advisable to form a new balancing group. A method of centralized adjustment of producers' forecasts is proposed in order to reduce the cost of covering the imbalances of the members of the balancing group. The method is based on the use of coefficients calculated by optimizing the objective function, which takes into account the interest of the balancing group as a whole and each individual participant. Calculations have shown that the application of this method reduces the cost of imbalances for most model balancing groups. References 9, figures 2.